2013
DOI: 10.4049/jimmunol.1200492
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Innate Immune Activation by Surface Texturing of Polymer Microparticles: The Role of Shape in Inflammasome Activation

Abstract: Polymeric microparticles have been widely investigated as platforms for delivery of drugs, vaccines, and imaging contrast agents, and are increasingly used in a variety of clinical applications. Microparticles activate the inflammasome complex and induce the processing and secretion of IL-1β, a key innate immune cytokine. Recent work suggests that while receptors are clearly important for particle phagocytosis, other physical characteristics especially shape, play an important role in the way microparticles ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 49 publications
2
66
1
Order By: Relevance
“…For example, it has been shown that proteins and opsonins may adsorb more favourably onto a hydrophobic surface, promoting recognition, uptake and inflammatory signaling by phagocytic cells (Ruge et al, 2012;Singh & Lillard, 2009). A pertinent mechanism in this study may be particle aggregation in physiological fluids resulting in irregular surfaces, which have been associated with higher inflammatory potential than comparable smooth-surface particles (Vaine et al, 2013). Only the nanoparticles in the high surface hydrophobicity group (PS50 and PVAc80) aggregated in isotonic buffer at 37 C ( Table 1), suggesting that this may occur to some extent in vivo and contribute to their enhanced toxicity profile.…”
Section: Discussionmentioning
confidence: 96%
“…For example, it has been shown that proteins and opsonins may adsorb more favourably onto a hydrophobic surface, promoting recognition, uptake and inflammatory signaling by phagocytic cells (Ruge et al, 2012;Singh & Lillard, 2009). A pertinent mechanism in this study may be particle aggregation in physiological fluids resulting in irregular surfaces, which have been associated with higher inflammatory potential than comparable smooth-surface particles (Vaine et al, 2013). Only the nanoparticles in the high surface hydrophobicity group (PS50 and PVAc80) aggregated in isotonic buffer at 37 C ( Table 1), suggesting that this may occur to some extent in vivo and contribute to their enhanced toxicity profile.…”
Section: Discussionmentioning
confidence: 96%
“…Nanoparticles, whether environmental [6,10], endogenously formed [7,8] or engineered for downstream applications [5,9] have been well studied and clearly linked to inflammasome activation. However, in vitro studies have on occasions been difficult to reconcile with in vivo situations [14,16,40], suggesting that applied in vitro experimental conditions do not always reflect in vivo outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, the late Jurg Tschopp and colleagues reported on the activation of the inflammasome by uric acid and calcium phosphate crystals [4]. Since then, numerous (engineered) nanoparticles have been attributed as inflammasome activators, including silica, titanium dioxide, aluminium hydroxide and calcium phosphates [5][6][7][8][9][10].…”
mentioning
confidence: 97%
“…Studies have shown that elongated particles are trafficked toward the nucleus and are oriented tangentially when compared with spherical particles, which are trafficked quickly and exhibit hexagonal packing in the cell (38, 40). Additionally, budding, or highly textured, microparticles have been shown to activate neutrophils significantly more than smooth particles (41) (Figure 2 a – b ). Further, budding particles were more readily phagocytosed than smooth particles and induced more lipid-raft recruitment to the phagosome.…”
Section: Effects Of Biomaterials On Immune Cells and Immunomodulamentioning
confidence: 99%